Big Data Analytics Capabilities and Competitive Advantage in Batik SMEs: The Mediating Roles of SCM and E-CRM - Nanang Adie Setyawan; Bagus Yunianto Wibowo; Novitasari Eviyanti; Irin Mirrah Luthfia; Eva Purnamasari (LP2M IAIN Palopo, 2025)
This study contributes to sustainable supply chain literature by integrating organizational and institutional perspectives within the context of traditional creative industries. This study examines how Big Data Analytics Capabilities (BDAC) contribute to sustainable performance and competitive advantage among batik micro, small, and medium enterprises (MSMEs) in Central Java. Grounded in the Resource-Based View (RBV), the research investigates the mediating roles of Supply Chain Management Capabilities (SCMC), Electronic Customer Relationship Management (e-CRM), and Circular Economy Practices (CEP) in translating data-driven capabilities into sustainability outcomes. A quantitative explanatory approach was employed using survey data collected from 150 batik MSME owners and managers across major batik-producing regions in Central Java. Data were analyzed using Structural Equation Modeling (SEM) with AMOS. The results demonstrate that BDAC has a significant positive effect on SCMC, e-CRM, and CEP. Furthermore, BDAC directly influences sustainable performance, while SCMC, e-CRM, and CEP partially mediate this relationship. Sustainable performance, in turn, significantly enhances competitive advantage. The structural model exhibits strong goodness-of-fit indices, indicating robustness and explanatory power. These findings confirm that data-driven capabilities alone are insufficient to generate competitive advantage unless they are operationalized through supply chain integration, digital customer relationship management, and circular economy practices. This study contributes to the literature by integrating big data analytics, sustainability, and competitive advantage within the context of traditional creative MSMEs. Practically, the results provide strategic guidance for MSME owners and policymakers in leveraging digital transformation to achieve sustainable and competitive business performance